Four sessions of repeated-sprint cycling training with or without severe hypoxia do not modify overground running sprint force-velocity profile - Brocherie, F.; Racinais, S.; Couderc, A.; Piscione, J.; Girard, O. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To investigate the effect of cycling-based repeated-sprint training in hypoxia versus in normoxia on single overground running sprint performance and associated force-velocity (F-V) profile in world-class female rugby sevens players.